The Implementation of Curriculum by Using Motion Pattern-Based Learning Media for Pre-school Children - Yusmawati, Yusmawati; Lubis, Johansyah (Jurnal Pendidikan Usia Dini, 2019)
This study aims to determine the implementation of curriculum in learning activities of pre-school children and develop motion pattern-based learning media for pre-school children. This research was carried out in thirty kindergartens in East Jakarta. It was conducted in 4 months, from June to October 2018. This research is included in the development and evalu-ation research (mixed method). The scope of the research is the implementation of curricu-lum and the development of learning media for pre-school children by using customized tools. Data was collected by using questionnaires and analyzed by using Guttman scale and Likert scale. Percentage of the implementation of learning for preschoolers in Kindergarten in East Jakarta is very good. The goal dimension got 98.2%, the content dimension got 99.3%, the method dimension got 99.3% and the evaluation dimension got 98.3%. The product of this study is a learning media that is adjusted to the implementation of motion pattern-based learning activities for pre-school children. Keywords: Early childhood education curriculum, Motion Pattern-Based Learning Media, Pre-school children References Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Asdi Mahasatya. Arikunto, S. (2014). Prosedur Penelitian. Jakarta: Rineka Cipta. Ayob, A., Badzis, M., & Nordin, A. L.Abdullah, R. (2016). Kurikulum Permata Negara. Tanjong Malim: NCDRC, UPSI. Azia, R. S. (1976). Curriculum Principles and Foundation. New York: Harper and Row Publisher. Boyle, T., & Phelps, R. (2010). Curriculum To Acknowledge Diversity. The International Journal of Learning, 17(2), 357–370. Brady, L. (1995). Curriculum development (5th ed.). Sydney: Prentice-Hall. Cholimah, N. (2012). Pengembangan Kurikulum PAUD Berdasarkan Permen 58 Tahun 2009. Criticos. (1996). Media. Amazon. George A.Beauchamp. (1981). Curriculum Theory. F.E. Peacock Publisher. Jamaris, M. (2006). Perkembangan dan Pengembangan Anak Usia Dini Taman Kanak-kanak. Jakarta: Gramedia Widiasarana. Johnson, M. (1967). Intentionality in Education. New York: Center for Curriculum Research and Services. Kawaitouw, Y. I., Widiastuti, A. A., & Kurniawan, M. (2018). Unit Studies Curriculum: Strategi Guru Dalam Implementasi Kurikulum di Jungle School Sidomukti. Jurnal Pendidikan Usia Dini, 12(November), 371–380. Kerlinger, F. N. (1990). Asas-asas Penelitian Behavioral (3th ed.). Yogyakarta: Gajah Mada University Press. Langgulung, H. (1989). Manusia dan Pendidikan: Suatu Analisa Psikologik dan Pendidikan. Jakarta: Pustaka al-Husna. MacDonald, J. B. (1965). Educational Models for Instruction. Washington DC: The Association for Supervision and Curriculum Development. Morrison, G. S. (2012). Dasar-dasar Pendidikan Anak Usia Dini. Jakarta: Indeks. Olivia, P. F. (1992). Developing the Curriculum (Third Edit). New York: Harper Collins Publishers Inc. Ornstein, A. C. (2004). Curriculum:Foundation, Principles, and Issues. Boston: Pearson Education, Inc. Ozturk, I. H. (2011). Curriculum Reform and Teacher Autonomy in Turkey: the case of the History Teaching". International Journal of Instruction, 4 (2)(2), 113–127. Prihatini, P. (2014). Kajian Ide Kurikulum 2012 PAUD dan Implikasinya dalam Pengembangan KTSP. Cakrawala: Jurnal Pendidikan Anak USia Dini. Rahelly, Y. (2018). Implementasi Kurikulum 2013 Pendidikan Anak Usia Dini di Sumatera Selatan. Jurnal Pendidikan Usia Dini, 12(November), 381–390. https://doi.org/https://doi.org/10.21009/JPUD.122.19 Rohmansyah, N. A. (2017). Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemahaman Konsep Pendidikan Jasmani Pada Pembelajaran Tematik Terintegrasi Siswa Kelas IV. JURNAL PENJAKORA, 4(28–35). Saylor, J. G., & Alexander, W. M. (1981). Curriculum Planning for Better Teaching and Learning. Holt-Rinehart and Winston. Sujiono, Y. N. (2009). Konsep Dasar Pendidikan Anak Usia Dini. Jakarta: Indeks. Sukmadinata, N. S. (2000). Pengembangan Kurikulum Teori dan Praktek. Bandung: Remaja Rosdakarya. Sutapa, P. (2014). Pengembangan Model Pembelajaran Pendidikan Jasmani Berbasis Kinestetik Untuk Anak Usia Pra Sekolah. Yogyakarta. Webster. (1993). Webster’s New International Dictionary. GC Company. Widoyoko, E. P. (2012). Evaluasi Program Pembelajaran. Yogyakarta: Pustaka Pelajar. Winarno. (2011). Winarno. Metodologi dalam Penelitian Pendidikan Jasmani. Malang: Media Cakrawala Press. Winarso, W. (2017). Dasar Pengembangan Kurikulum Sekolah, (January 2015).